Economic versus non-economic motives of transhumant farmers in Greece - Ragkos A.; Mitsopoulos I.; Kiritsi S.; Piteris C.; Lymberopoulos A.; Palla E.; Bampidis V.; Lagka V. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Transhumance in Greece constitutes a paradigm of a multifunctional system, affecting the environment and the viability of mountainous areas, while its continuation is linked to the cultural identity of these areas, including the maintenance of the transhumant farmer profession itself. This study proposes a conceptual framework to approach the multifunctional character of transhumance. Through a questionnaire survey, a latent construct measuring the degree to which transhumant farmers are motivated by their multiple roles in their decision-making process was proposed. In order to examine the validity of this latent construct, a confirmatory factor analysis was employed, revealing that farmers incorporate economic and non-economic features within the same framework, thus understanding that they play distinct roles, all of which comprise the multifunctional character of their profession. Not surprisingly, economic features are negatively correlated with non-economic ones, providing an explanation as to why transhumance has demonstrated resilience under harsh economic conditions. The results can be used in the implementation of Reg. EC/1305/2013, as they highlight that funds for transhumance should not be of purely economic nature, but should also be allocated to sectors affected by the multifunctional character of the system.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)